Incident Prevention and Mitigation In The Asia Pacific Littorals: Framing, Expanding, and Adding to Cues - Ong-Webb, Graham (2017)
This paper explores the possibility of South China Sea claimants and regional countries playing an active role in developing measures to prevent untoward incidents involving government (including naval and maritime law enforcement) and non-government vessels while political negotiations take place with respect to the proposed Code of Conduct between ASEAN and China. It argues that such a comprehensive incident prevention and mitigation plan must be multidimensional and multilevel in its approach, cascading from the political, strategic, operational, to tactical levels. This study breaks down into three main sections. The first examines the framing of the existing Code for Unplanned Encounters at Sea (CUES) and its expansion as well as any new prevention and mitigation initiatives. The center of gravity and theory of success for CUES must be at operational and tactical levels, this paper highlights, while also proposing that CUES should be expanded to include sub-surface and aerial- based actions as other potential triggers for unplanned encounters and unintended escalations at sea. The end-state calls for a comprehensive CUES in light of the multidimensional nature of the SCS maritime landscape. The second section of this paper assesses the prospects for an expanded CUES, focusing on maritime law enforcement and irregular forces. It examines the viability of expanding this mechanism through what this paper terms as “Phased” and “Blanket” Approaches, which is dependent on the regional political climate. The third, final section raises two proposals at the strategic level, and six proposals pegged at the operational and tactical levels of planning and activity to build on and enhance the existing slate of such mechanisms as CUES to promote navigational safety and risk reduction in regional waters.